Pendampingan optimalisasi penggunaan google form untuk pembelajaran daring di masa pandemi - Djamdjuri, Dewi Suriyani; Kholisah, Fadia (Penamas: Journal of Community Service, 2022)
Since the COVID-19 pandemic took place, the issue that teachers face, particularly in the regions, is a lack of knowledge in creating learning media that can be used in online learning. To overcome this problem, our team held training on making Google Form for elementary school teachers. The method we provide in this community service activity is by providing direct training to elementary school teachers and providing assistance in making learning media using the Google Form. The results of this service activity are that the teachers who participated in the training understood the technique of using, creating, and designing their own Google Form according to the needs of each subject as an online learning medium; all the teachers who participated in the training were happy, interested, and very enthusiastic about the Google Form training activities; and the results of the questionnaire completed by the teachers who attended the training showed that 90% of the teachers would apply Google Form as a medium of learning in teaching and learning activities.